2016
DOI: 10.1634/theoncologist.2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Breast Camps for Awareness and Early Diagnosis of Breast Cancer in Countries With Limited Resources: A Multidisciplinary Model From Kenya

Abstract: Background. Breast cancer is the most common cancer of women in Kenya. There are no national breast cancer early diagnosis programs in Kenya. Objective. The objective was to conduct a pilot breast cancer awareness and diagnosis program at three different types of facilities in Kenya. Methods. This program was conducted at a not-for-profit private hospital, a faith-based public hospital, and a government public referral hospital. Women aged 15 years and older were invited. Demographic, risk factor, knowledge, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…The identification of approximately 1% breast cancer (0.2% to 1.4% of all screened women; Table 1 ) during our community CBE screening campaign is comparable to that which has been described by others, 20 - 24 including findings from a large community-based, clustered randomized control study using trained health care workers in India. 20 In general, one in 10 women who present at community screening campaigns will have an abnormal CBE, and approximately 1% of the screened population will be diagnosed with breast cancer.…”
Section: Discussionsupporting
confidence: 86%
“…The identification of approximately 1% breast cancer (0.2% to 1.4% of all screened women; Table 1 ) during our community CBE screening campaign is comparable to that which has been described by others, 20 - 24 including findings from a large community-based, clustered randomized control study using trained health care workers in India. 20 In general, one in 10 women who present at community screening campaigns will have an abnormal CBE, and approximately 1% of the screened population will be diagnosed with breast cancer.…”
Section: Discussionsupporting
confidence: 86%
“…It should be done adequately by trained health workers [18]. The role of self-examination and clinical breast examination is important in areas where mammography may not be available for financial and accessibility reasons [19]. In addition, statistics indicate that 90% of breast nodules are discovered by women themselves [19].…”
Section: Discussionmentioning
confidence: 99%
“…Alerta Rosa: Breast Cancer Navigation in Mexico self-examination behaviors and increase the likelihood of BC screening attendance [18]. In our program, media exposure led not only to increased awareness but also to three BC diagnosis in asymptomatic patients, as in the Kenya study [16].…”
Section: Discussionmentioning
confidence: 80%
“…Preliminary findings of a randomized controlled study from the Cairo Breast Screening trial demonstrated that screening based on breast self-examination combined with clinical evaluation resulted in downstaging of tumors in the intervention arm compared with the control arm [15]. A study from Kenya showed that conducting a multidisciplinary BC awareness and early diagnosis program in LMICs is feasible and can be a model for increasing BC awareness and early diagnosis in countries with limited resources [16], but that program differs from ours by the fact that it was targeted for the general population instead of only symptomatic patients, which resulted in a lower percentage of BC diagnoses (1%). Finally, a third report from Boston established that patient navigation significantly decreased the time to diagnosis among patients with a BC screening abnormality that was diagnosed after 60 days since detection (hazard ratio, 1.40; 95% confidence interval, 1.1-1.9), with no differences before that period [17].…”
Section: Discussionmentioning
confidence: 99%